ANALISIS KEMAMPUAN KONEKSI MATEMATIK SISWA MTs DITINJAU DARI SELF CONFIDENCE - Pipit Pitriyani; Aflich Yusnita Fitrianna; Pamila Malinda; Mira Siti Hajar (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACT This research aims to describe what extent student’s mathematical connection ability that reviewed from self confidence and seen from error in completed  the mathematical connection test. The subject of this research is students of MTs Fatahillah Cimahi class VIIIB as much 22 students. The method used in this research was descriptive method with qualitative approach. The step of this research that composed from 4 step:  namely self confidence questionnaire, mathematical connection ability test, data analysis and draw conclusion. The result showed that 1) Students with high self confidence do errors on identify relation of one procedure to other procedure in same representation and explain mathematics application topic in field of study content or daily problem; 2) Students with medium self confidence do errors in identify relationship of one procedure to other procedure in same representation and do error in identify various relationship of concept representation and mathematics procedure; and 3) Students with low self confidence do error on identify relationship of one procedure to other procedure in same representation. The conclusion of this research is student’s mathematical connection ability still less. Keywords : Ability Connection Mathematics, Self Confidence, Error Analysis